A hydrophilic magnetic nanomaterial and its preparation method and application

CN114053966BActive Publication Date: 2025-01-10NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111221837.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-04
Filing Date
2021-10-20
Publication Date
2025-01-10
Estimated Expiration
2041-10-20

AI Technical Summary

Technical Problem

在此过程中,其Ms也会大大减弱,从而最终影响其MR成像性能

Benefits of technology

[0076] Unless otherwise specified, the numerical range represented by "-" or "~" includes the endpoint value and the value between the two endpoints. For example, 10~24h includes 10h and 24h, and the value between 10h and 24h.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114053966B_ABST
    Figure CN114053966B_ABST
Patent Text Reader

Abstract

The present application discloses a preparation method and application of a hydrophilic magnetic nanomaterial. The preparation method comprises the following steps: reacting a raw material I containing an iron source, an M source, an alkali source, and water to obtain the hydrophilic magnetic nanomaterial; the M is selected from any one of transition metal elements; the molar ratio of the iron source to the M source is 3.6:0-1.8; the M source is not 0; the iron source is measured in moles of iron, and the M source is measured in moles of M. The synthesis method is simple to operate and low in cost, and also avoids the surface modification step, laying a material foundation for subsequent integrated diagnosis and treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a hydrophilic magnetic nanomaterial and a preparation method and application thereof, belonging to the technical field of biomaterials. Background Art

[0002] In the past half century of scientific research, magnetic micro / nanoparticles (MNPs) have attracted the attention of scientists due to their special magnetic and electrical properties. Major breakthroughs have been achieved in new methods for synthesizing unique nanoparticle shapes and composite structures to a variety of MNPs characterization techniques, and they have also been widely used in fields such as biomedicine and nanotechnology, such as bioimaging, targeted drug delivery, biosensors, magnetic hyperthermia, tissue repair and cell sorting. Therefore, the controllability of MNPs will help to independently design and prepare nanoparticles with special functions, thereby improving their effectiveness.

[0003] Reasonable tuning of the properties of MNPs will help to design and optimize magnetic nanoparticles for special needs, thereby improving the overall effect of the material. The size, shape, composition and structure of magnetic nanoparticles will affect the saturation magnetization (Ms), coercivity (Hc), Curie temperature (T B ) and relaxation time (t N and t B ) and other properties. However, among the many influencing factors, adjusting the divalent transition metal (such as Mn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ 、Zn 2+ ) is also an important means. Fe3O4 has an inverse spinel crystal structure, and there are tetrahedral positions (T d ) and octahedral positions (O h ) of Fe ions, of which Fe 3+ O h :Fe 2+ O h :Fe 3+ T d =1:1:1, when divalent transition metal ions are doped into it, they will selectively replace the iron ions located at different lattice positions, thereby changing the crystal structure of ferrite and M 2+ The lattice occupancy of the iron ions changes the overall magnetic moment, and the corresponding saturation magnetization also changes significantly. Therefore, by doping the ferrite with divalent transition metal ions, the magnetic properties of the magnetic nanomaterial can be precisely controlled by changing the magnetic moment and saturation magnetization of the material.

[0004] In addition, stable, finely controllable magnetic properties are key indicators for determining whether MNPs are used as contrast agents for magnetic resonance imaging (MRI). Among them, one of the most important parameters affecting the MRI imaging contrast of MNPs is the magnetic doping effect. When different divalent transition metals are doped into ferrite, the saturation magnetization (Ms) will be directly affected. The change of Ms will affect the imaging contrast effect of MR. In addition, the doping of divalent transition metal ions may depend on the potential mechanism of different synthesis methods. For different synthesis systems, the optimal doping amount is different. At present, most of the synthesis methods of MNPs are through high-temperature decomposition of iron oleate precursors, but the MNPs prepared in this way are often hydrophobic. Given that hydrophilicity is one of the key indicators that determine whether it can be used inside the body, the surface is modified to make it change from oil phase to water phase. In this process, its Ms will also be greatly weakened, which will ultimately affect its MR imaging performance. Summary of the invention

[0005] According to one aspect of the present application, a method for preparing a hydrophilic magnetic nanomaterial is provided. The synthesis method is simple to operate and low in cost, and also avoids the surface modification step, thus laying a material foundation for subsequent integrated diagnosis and treatment.

[0006] A method for preparing a hydrophilic magnetic nanomaterial, the preparation method comprising the following steps:

[0007] Reacting a raw material I containing an iron source, an M source, an alkali source, and water to obtain the hydrophilic magnetic nanomaterial;

[0008] The M is selected from any one of transition metal elements;

[0009] The molar ratio of the iron source to the M source is 3.6:0-1.8;

[0010] The M source is not 0;

[0011] The iron source is calculated based on the molar number of iron, and the M source is calculated based on the molar number of M.

[0012] Optionally, the upper limit of the molar ratio of the iron source to the M source is selected from 3.6:0.1, 3.6:0.5, 3.6:0.8, 3.6:1, 3.6:1.2, 3.6:1.5 or 3.6:1.8; the lower limit is selected from 3.6:0.5, 3.6:0.8, 3.6:1, 3.6:1.2, 3.6:1.5 or 3.6:1.8.

[0013] Optionally, M is selected from any one of Zn, Mn, Fe, Co and Ni.

[0014] Optionally, the iron source includes at least one of iron salts;

[0015] The M source includes at least one of the M salts;

[0016] The alkali source includes at least one of alkali solutions.

[0017] Optionally, the iron salt includes at least one of ferrous sulfate, ferrous sulfate heptahydrate, ferric chloride hexahydrate, ferrous chloride tetrahydrate, and ferric nitrate nonahydrate;

[0018] The M salt includes at least one of an M-containing acetate, an M-containing nitrate, an M-containing chloride, and an M-containing sulfate.

[0019] The M salt includes at least one of zinc acetate dihydrate, zinc sulfate, zinc nitrate hexahydrate, and zinc chloride.

[0020] The alkaline solution includes at least one of hydrazine monohydrate solution, ethylene glycol solution, sodium hydroxide solution, ammonia water, and triethanolamine solution.

[0021] Optionally, the concentration of the alkaline solution is 10-20 mM.

[0022] Optionally, the ratio of the iron source, M source, alkali source and water satisfies:

[0023] Iron source: M source: alkali source: water = 3.6mmol: 0-1.8mmol: 5-15mL: 30-50mL;

[0024] The M source is not 0;

[0025] The iron source is calculated based on the molar number of iron, and the M source is calculated based on the molar number of M.

[0026] Optionally, iron source: M source: alkali source: water = 3.6 mmol: 0.1-1.8 mmol: 8-15 mL: 40-50 mL.

[0027] Optionally, iron source: M source: alkali source: water = 3.6 mmol: 0.5-1 mmol: 5-10 mL: 30-40 mL.

[0028] Optionally, the raw material I also includes a surfactant.

[0029] Optionally, the surfactant includes at least one of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, triethanolamine, aspartic acid, glycine, sodium citrate, bovine serum albumin, 1,3-dialkylacetone, and polyethylene glycol.

[0030] Optionally, the molar ratio of the surfactant to the iron source is 0.2 to 2:3.6.

[0031] Optionally, the upper limit of the molar ratio of the surfactant to the iron source is selected from 0.5:3.6, 0.8:3.6, 1:3.6, 1.2:3.6, 1.5:3.6, 1.8:3.6 or 2:3.6, and the lower limit is selected from 0.2:3.6, 0.5:3.6, 0.8:3.6, 1:3.6, 1.2:3.6, 1.5:3.6 or 1.8:3.6.

[0032] Optionally, the reaction conditions include:

[0033] The reaction temperature is 140-200°C;

[0034] Optionally, the reaction conditions further include:

[0035] The reaction time is 10 to 16 hours.

[0036] Optionally, the upper limit of the temperature is selected from 150, 160 or 180°C; the lower limit is selected from 140, 150 or 160°C.

[0037] Optionally, the upper limit of the time is selected from 12, 14 or 16 hours; the lower limit is selected from 10, 12 or 14 hours.

[0038] Optionally, the raw material I is obtained by the following steps: mixing an iron source, an M source and water and stirring I, adding an alkali source and stirring III to obtain the raw material I.

[0039] Optionally, the stirring I is performed until the iron source and the M source are completely dissolved and a color change is observed.

[0040] Optionally, the stirring I is performed until the mixture is completely dissolved.

[0041] Optionally, a surfactant is added to the mixture obtained by stirring I, and stirring II.

[0042] Optionally, the stirring step II is performed until the color of the solution gradually changes from light green to light yellow-green.

[0043] Optionally, the stirring time of stirring II is 2 to 3 minutes.

[0044] Optionally, the stirring step III is performed until the color of the precipitate changes from blue-green to dark green.

[0045] Optionally, the stirring time of the stirring III is 25 to 35 minutes.

[0046] Optionally, the addition rate of the alkali source is about 40 to 80 minutes.

[0047] According to another aspect of the present application, a hydrophilic magnetic nanomaterial is provided. The hydrophilic magnetic nanomaterial has a high saturation magnetization intensity, can enhance MRI imaging contrast, and has near-infrared I region photothermal performance.

[0048] The hydrophilic magnetic nanomaterial is prepared according to any one of the preparation methods described above.

[0049] Optionally, the hydrophilic magnetic nanomaterial is a magnetic nanomaterial of ferrite doped with divalent transition metal ions, selected from at least one of the compounds having the chemical formula shown in Formula I;

[0050] M x Fe 3-x O4 formula I;

[0051] The value range of x is 0.1 to 1.

[0052] Optionally, the average particle size of the hydrophilic magnetic nanomaterial is 20 to 40 nm.

[0053] Optionally, the upper limit of the average particle size of the hydrophilic magnetic nanomaterial is selected from 25, 30 or 35 nm; the lower limit is selected from 20, 25 or 30 nm.

[0054] Optionally, the average particle size of the hydrophilic magnetic nanomaterial is 20 to 30 nm.

[0055] Optionally, the hydrophilic magnetic nanomaterial has photothermal performance and / or MRI imaging performance of T2 imaging at 780-1000 nm.

[0056] Optionally, the photothermal performance of the hydrophilic magnetic nanomaterial is specifically manifested as having a good photothermal effect at 808nm (near infrared I region); and the MRI imaging performance is specifically manifested as T2 imaging (dark imaging).

[0057] According to another aspect of the present application, there is provided a hydrophilic magnetic nanomaterial prepared according to any one of the preparation methods described above or an application of at least one of the hydrophilic magnetic nanomaterials described above in the biomedical field.

[0058] Optionally, the application is the use of the hydrophilic magnetic nanomaterial in the preparation of magnetic resonance imaging agents and / or photothermal therapy drugs.

[0059] The hydrophilic magnetic nanomaterial prepared by the preparation method provided in the present application is a magnetic nanomaterial of ferrite doped with divalent transition metal ions, which has the characteristics of high saturation magnetization, hydrophilicity, small particle size, ranging from about 20 to 30 nm, and strong absorption of near-infrared light.

[0060] The divalent transition metal ion may be Zn 2+ , Mn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ Any one of the above.

[0061] The preparation method comprises the following steps:

[0062] Step 1: Weigh a certain amount of ferrous sulfate heptahydrate (FeSO4·7H2O) and a certain amount of zinc acetate dihydrate (Zn(OAc)2·2H2O), add deionized water thereto, and stir until they are completely dissolved and a color change is observed;

[0063] Step 2: Then add a certain amount of sodium citrate, stir until dissolved, add hydrazine monohydrate solution, stir for a period of time, take a certain amount of reaction solution and put it into the inner tank of the reactor, and put it into a high-temperature oven for high-temperature hydrothermal reaction;

[0064] Step 3: The reaction is cooled to room temperature, washed and centrifuged, and after centrifugation and washing, the obtained sample is stored for later use.

[0065] Optionally, in step 1: the amount of FeSO4·7H2O weighed is about 3.6 mmol, the amount of Zn(OAc)2·2H2O added is 0 mmol to 2 mmol, and the volume of deionized water added is 30 to 50 mL.

[0066] Optionally, in step 1: after continuing to stir, there will be a color change, and the color of the solution gradually changes from light green to light yellow-green.

[0067] Optionally, in step 2: the amount of sodium citrate added is 0.2mmol to 2mmol, the amount of N2H4·H2O added is 5mL to 15mL, the concentration is 10M to 20M, the sodium citrate is added and stirred until dissolved, and its color will gradually change to light green, and the N2H4·H2O must be added slowly dropwise, and the solution changes from light green to blue-green precipitate.

[0068] Optionally, in step 2: the N2H4·H2O is added and stirred for a period of time, and the precipitate is poured into the reactor when the color changes from blue-green to dark green. The high-temperature hydrothermal reaction temperature is 140°C to 200°C, and the reaction time is 10h to 16h.

[0069] Optionally, in step 3: the solvents used for washing are anhydrous ethanol and deionized water, and the washing is performed alternately for 5-8 times, the centrifugal speed is about 5000-10000 rpm, and the centrifugal time is 8-12 min.

[0070] Optionally, in step 3: the product can be stored in a freeze dryer for 10 to 24 hours for later use, or directly dispersed in deionized water or anhydrous ethanol and stored in a low temperature environment for later use.

[0071] The synthesis method is simple and convenient, has low production cost, can be prepared on a large scale, and is green and pollution-free. The saturation magnetization intensity of the ferrite doped with divalent transition metals is significantly improved. As an MRI contrast agent, the contrast of nuclear magnetic resonance imaging is significantly improved. In addition, the Zn x Fe 3-x O4 has an obvious photothermal effect in the near-infrared I region (780-1000nm), thus realizing the integration of diagnosis and treatment without additional complex modifications.

[0072] As an embodiment, the present application proposes a method based on a divalent transition metal ion Zn 2+ The single-doped ferrite magnetic nanomaterials were synthesized in one step by high-temperature hydrothermal method. x Fe 3-x O4 (x is the percentage of Zn content) nanomaterials.

[0073] The present application provides a Zn with high saturation magnetization, hydrophilicity, and a particle size of about 20 to 40 nm. x Fe 3- x The synthesis method of O4 magnetic nanomaterials, the specific technical route is as follows:

[0074] First, weigh about 3.6mmol of ferrous sulfate heptahydrate (FeSO4·7H2O), add a certain amount of zinc acetate dihydrate (Zn(Ac)2·2H2O), add 30-50mL of deionized water, put in a magnetic bar, stir until it is completely dissolved, and the solution gradually turns light yellow. Then add a certain amount of trisodium citrate dihydrate, stir until the color of the solution changes from light yellow to light green, and then slowly add 5-10mL of hydrazine monohydrate solution (10mol·L -1 N2H4·H2O), at this time, the solution gradually produces a blue-green precipitate. After stirring for a period of time, the solution turns into a dark blue-green precipitate. A certain amount of reaction solution is placed in the inner tank of the reactor, and placed in a high-temperature oven. The temperature is set between 140°C and 200°C, and the heating time is set between 10 and 16 hours.

[0075] After the reaction is cooled to room temperature, the supernatant is removed, the lower product is taken, and it is repeatedly washed with anhydrous ethanol and deionized water for several times. When centrifuged in a centrifuge, the speed is about 5000-10000rpm, and the centrifugation time is 8-12min. After centrifugation and washing, the obtained sample can be dried in a freeze dryer for 10-24h for standby use, or directly dispersed in deionized water, anhydrous ethanol and stored in a low temperature environment for standby use.

[0076] Unless otherwise specified, the numerical range represented by “-” or “~” includes the endpoint value and the values ​​between the two endpoints. For example, 10~24h includes 10h and 24h, and the values ​​between 10h and 24h.

[0077] The beneficial effects of this application include:

[0078] (1) The method for preparing the hydrophilic magnetic nanomaterial provided in the present application is to carry out the reaction in an inorganic solvent (alkaline aqueous solution), and the obtained product does not need surface modification to obtain the hydrophilic magnetic nanomaterial.

[0079] (2) The preparation method of the hydrophilic magnetic nanomaterial provided in the present application can effectively reduce the particle size of the hydrophilic magnetic nanomaterial and increase its hydrophilicity by adding a surfactant.

[0080] (3) The hydrophilic magnetic nanomaterial provided in the present application is a hydrophilic divalent transition metal ion-doped ferrite magnetic nanomaterial with high saturation magnetization and small particle size prepared by a one-step synthesis method. It has the advantages of simple synthesis method, low production cost, large-scale preparation, green and pollution-free. Divalent transition metal ions are doped into ferrite, which selectively replaces iron ions at different positions, thereby changing its crystal structure and optimizing the performance of ferrite. The saturation magnetization of the ferrite material doped with divalent transition metals is significantly improved. As an MRI contrast agent, its nuclear magnetic resonance imaging contrast is significantly improved. In addition, the hydrophilic magnetic nanomaterial obtained by the synthesis method has an obvious photothermal effect in the near-infrared I region (780-1000nm), and the lesion site can be imaged and effectively photothermally treated at the same time, thereby achieving an integrated diagnosis and treatment effect without additional complex modifications. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] Figure 1 is Zn in Example 2 0.2 Fe 2.8 Scanning electron microscope image of O4 magnetic nanomaterials.

[0082] Figure 2 is Zn in Example 3 0.3 Fe 2.7Scanning electron microscope image of O4 magnetic nanomaterials.

[0083] Figure 3 is Zn in Example 5 0.5 Fe 2.5 Scanning electron microscope mapping spectrum of O4 nanomaterials; A is Zn 0.5 Fe 2.5 Scanning electron microscope image of O4; B is Zn 0.5 Fe 2.5 Distribution diagram of the three elements Zn, Fe, and O on O4; C is the distribution diagram of Fe in the sample under the field of view; D is the distribution diagram of O in the sample under the field of view; E is the distribution diagram of Zn in the sample under the field of view.

[0084] Figure 4 It is the high-resolution diffraction pattern of the ZnFe2O4 nanomaterial in Example 7.

[0085] Figure 5 is Zn in Example 10 0.2 Fe 2.8 Near-infrared photothermal effect diagram of O4 nanomaterials. DETAILED DESCRIPTION

[0086] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0087] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0088] Example 1 - Preparation of Zn with an average particle size of 20 nm 0.1 Fe 2.9 O4 magnetic nanomaterials:

[0089] Take 3.6mmol FeSO4·7H2O, 0.0093mmol Zn(Ac)2·2H2O, add 40mL deionized water, then add 0.1858g trisodium citrate dihydrate (0.64mmol), stir until the color of the solution changes from light yellow to light green (stirring time is 3min), then slowly add 10mL N2H4·H2O (10mol·L -1 ) (addition rate is 60 drops / minute), after stirring for a period of time (stirring time is 30 minutes), take 25mL of the reaction solution and place it in the reactor liner, put it into a high-temperature oven, the temperature is 180°C, and the heating time is 10 hours. After the reaction is cooled to room temperature, it is repeatedly washed with anhydrous ethanol and deionized water several times. When centrifuged in a centrifuge, the speed is 10000rpm, and the centrifugation is 8 minutes. The obtained product is stored at low temperature for later use.

[0090] Example 2—Preparation of Zn with an average particle size of 20 nm 0.2Fe 2.8 O4 magnetic nanomaterials:

[0091] Take 3.6mmol FeSO4·7H2O, 0.0194mmol Zn(Ac)2·2H2O, add 40mL deionized water, then add 0.1858g trisodium citrate dihydrate, stir until the solution color changes from light yellow to light green (stirring time is 2min), then slowly add 10mL N2H4·H2O (10mol·L -1 ) (addition rate is 60 drops / minute), after stirring for a period of time (stirring time is 30 minutes), take 25mL of the reaction solution and place it in the reactor liner, put it into a high-temperature oven, the temperature is 180℃, and the heating time is 10 hours. After the reaction is cooled to room temperature, it is washed alternately with anhydrous ethanol and deionized water for 3 times each. When centrifuged in a centrifuge, the speed is 10000rpm, and the centrifugation is 8 minutes. The obtained product is stored at low temperature for later use. The obtained Zn 0.2 Fe 2.8 Scanning electron microscope images of O4 magnetic nanomaterials Figure 1 As shown, the average particle size is 20 nm.

[0092] Example 3 - Preparation of Zn with an average particle size of 20 nm 0.3 Fe 2.7 O4 magnetic nanomaterials:

[0093] Take 3.6mmol FeSO4·7H2O, 0.301mmol Zn(Ac)2·2H2O, add 40mL deionized water, then add 0.1858g trisodium citrate dihydrate, stir until the color of the solution changes from light yellow to light green (stirring time is 3min), then slowly add 10mL N2H4·H2O (10mol·L -1 ) (addition rate is 60 drops / minute), after stirring for a period of time (stirring time is 30 minutes), take 25mL of the solution and place it in the reactor liner, put it into a high-temperature oven at 180°C for 12 hours. After the reaction is cooled to room temperature, it is washed alternately with anhydrous ethanol and deionized water for 3 times each, and centrifuged at a speed of 10000rpm for 8 minutes. The obtained product is stored at low temperature for later use. The obtained Zn 0.3 Fe 2.7 Scanning electron microscope images of O4 magnetic nanomaterials Figure 2 As shown, the average particle size is 20 nm.

[0094] Example 4 - Preparation of Zn with an average particle size of 20 nm 0.4 Fe 2.6 O4 magnetic nanomaterials:

[0095] Take 3.6mmol FeSO4·7H2O, 0.417mmol Zn(Ac)2·2H2O, add 40mL deionized water, then add 0.1858g trisodium citrate dihydrate, stir until the solution color changes from light yellow to light green (stirring time is 3min), then slowly add 10mL N2H4·H2O (10mol·L -1 ) (addition rate is 60 drops / minute), after stirring for a period of time (stirring time is 30 minutes), take 25mL of the reaction solution and place it in the reactor liner, put it into a high-temperature oven, the temperature is 180°C, and the heating time is 12 hours. After the reaction is cooled to room temperature, it is washed alternately with anhydrous ethanol and deionized water for 3 times each. When centrifuged in a centrifuge, the speed is 10000rpm, and the centrifugation is 8 minutes. The obtained product is stored at low temperature for later use.

[0096] Example 5—Preparation of Zn with an average particle size of 20 nm 0.5 Fe 2.5 O4 magnetic nanomaterials:

[0097] According to the technical route detailed in the content of the present invention, 3.6mmol FeSO4·7H2O, 0.542mmol Zn(Ac)2·2H2O were weighed, 40mL deionized water was added, and then 0.1858g trisodium citrate dihydrate was added, and stirred until the color of the solution changed from light yellow to light green (stirring time was 3min), at which time 10mL N2H4·H2O (10mol·L -1 ) (addition rate is 60 drops / minute), after stirring for a period of time (stirring time is 30 minutes), take 25mL of the reaction solution and place it in the reactor liner, put it into a high-temperature oven, the temperature is 180℃, and the heating time is 12 hours. After the reaction is cooled to room temperature, it is repeatedly washed with anhydrous ethanol and deionized water for several times. When centrifuged in a centrifuge, the speed is 10000rpm, centrifuged for 8 minutes, and the obtained product is stored at low temperature for later use. Zn 0.5 Fe 2.5 The scanning electron microscopy mapping spectrum of O4 nanomaterials is shown in Figure 3 As shown, where A is Zn 0.5 Fe 2.5 Scanning electron microscope image of O4; B is Zn 0.5 Fe 2.5 The distribution diagram of Zn, Fe and O on O4; C is the distribution diagram of Fe in the sample under the field of view; D is the distribution diagram of O in the sample under the field of view; E is the distribution diagram of Zn in the sample under the field of view, indicating that the three elements Zn, Fe and O are distributed in Zn x Fe 3-x O4 species are evenly distributed.

[0098] Example 6—Preparation of Zn with an average particle size of 20 nm 0.8 Fe 2.2 O4 magnetic nanomaterials:

[0099] According to the technical route detailed in the content of the present invention, 3.6mmol FeSO4·7H2O, 0.986mmol Zn(Ac)2·2H2O were weighed, 40mL deionized water was added, and then 0.1858g trisodium citrate dihydrate was added, and stirred until the color of the solution changed from light yellow to light green (stirring time was 2min), at which time 10mL N2H4·H2O (10mol·L -1 ) (addition rate is 60 drops / minute), after stirring for a period of time (stirring time is 30 minutes), take 25mL of the reaction solution and place it in the reactor liner, put it into a high-temperature oven at 180°C for 14 hours. After the reaction is cooled to room temperature, wash it alternately with anhydrous ethanol and deionized water for 3 times each, centrifuge it with a speed of 10000rpm, centrifuge for 8 minutes, and store the obtained product at low temperature for later use.

[0100] Example 7—Preparation of ZnFe2O4 magnetic nanomaterials with an average particle size of 20 nm:

[0101] According to the technical route detailed in the content of the present invention, 3.6mmol FeSO4·7H2O, 1.2mmol Zn(Ac)2·2H2O were weighed, 40mL deionized water was added, and then 0.1858g trisodium citrate dihydrate was added, and stirred until the color of the solution changed from light yellow to light green (stirring time was 3min), at which time 10mL N2H4·H2O (10mol·L -1 ) (addition rate is 60 drops / minute), after stirring for a period of time (stirring time is 30 minutes), take 25mL of the reaction solution and place it in the reactor liner, put it into a high-temperature oven, the temperature is 180°C, and the heating time is 14 hours. After the reaction is cooled to room temperature, it is washed alternately with anhydrous ethanol and deionized water for 3 times each. When centrifuged in a centrifuge, the speed is 10000rpm, centrifuged for 8 minutes, and the obtained product is stored at low temperature for later use. The high-resolution diffraction pattern of the obtained ZnFe2O4 nanomaterial is as follows Figure 4 As shown, it indicates that the obtained nanomaterial has relatively good crystallinity.

[0102] Example 8 - Hydrophilicity test of hydrophilic magnetic nanomaterials

[0103] The materials prepared in Examples 1-7 were freeze-dried respectively, and 10 mg of the dried sample was taken and added to a container containing 10 mL of deionized water. After 2 minutes of ultrasonication, the sample was completely dissolved in water. The dynamic particle size analyzer (DLS) was used for testing and found that the material was evenly and stably dispersed in water within 15 minutes, indicating that the material has good hydrophilicity and stability, and the PDI (polymer dispersibility index) value can reach 0.14.

[0104] Example 9—Zn x Fe 3-x MRI imaging performance test of O4 magnetic nanomaterials:

[0105] For Examples 1-7 with different doping amounts of Zn x Fe 3-x O4 was prepared into 1 mL of concentrations of 1mM, 0.5mM, 0.25mM, 0.125mM, 0.0625mM, 0.03125mM, and 0.015625mM, and then 1 mL of agar was added to fix it. Deionized water was used as the control group, and the test was carried out under a 1.5T nuclear magnetic resonance imaging instrument to measure its relaxation size and observe the changes in its dark imaging signal intensity with different concentrations and doping amounts.

[0106] The results show that the change trend of the r2 value of zinc-doped ferrite is consistent with the change trend of the saturation magnetization intensity, and when the zinc doping amount is 0.2, the r2 value reaches a maximum of 774mM. -1 S -1 It can be seen that when zinc is doped into ferrite at low concentration (x≤2), the MRI-T2 weighted imaging signal is significantly enhanced.

[0107] Example 10—Zn x Fe 3-x Photothermal performance test of O4 magnetic nanomaterials:

[0108] Weigh 600 μg Zn prepared in Examples 1 to 7 x Fe 3-x O4, add 3mL of deionized water to dissolve it, then take 1mL of the sample solution and place it in a cuvette, irradiate it with a laser with a wavelength of 808nm for 10min, and observe the change of the solution temperature over time. Take 1mL of deionized water and perform the same operation as above as the control group.

[0109] The results show that the material obtained by this synthesis method has a significant near-infrared photothermal effect. 0.2 Fe 2.8 O4 can heat up by about 20 degrees within 10 minutes under near-infrared light (e.g. Figure 5As shown in Figure 2, the photothermal effect is significant. And with the increase of zinc doping amount, its near-infrared photothermal conversion efficiency will gradually weaken.

[0110] Examples 11 to 13 - Preparation of hydrophilic magnetic nanomaterials

[0111] The difference between the preparation methods of Examples 11 to 13 and Example 7 is as shown in Table 1 below

[0112] Table 1 Differences between Examples 11 to 13 and Example 7

[0113]

[0114]

[0115] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a hydrophilic magnetic nanomaterial, characterized in that: The preparation method comprises the following steps: Reacting a raw material I containing an iron source, an M source, an alkali source, and water to obtain the hydrophilic magnetic nanomaterial; The raw material I also includes a surfactant; The surfactant comprises at least one of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, triethanolamine, aspartic acid, glycine, sodium citrate, bovine serum albumin, 1,3-dialkylacetone, and polyethylene glycol; The M source is an acetate containing Zn; The iron source is ferrous sulfate heptahydrate; The ratio of the iron source, M source, alkali source and water satisfies: Iron source: M source: alkali source: water = 3.6 mmol: 0~1.8 mmol: 5~15 mL: 30~50 mL; The M source is not 0; The iron source is measured in moles of iron, and the M source is measured in moles of M; The molar ratio of the surfactant to the iron source is 0.2-2:3.6; The hydrophilic magnetic nanomaterial has photothermal performance and / or MRI imaging performance of T2 imaging at 780 nm to 1000 nm.

2. The preparation method according to claim 1, characterized in that: The alkali source includes at least one of alkali solutions; The alkaline solution includes at least one of hydrazine monohydrate solution, ethylene glycol solution, sodium hydroxide solution, ammonia water, and triethanolamine solution.

3. The preparation method according to claim 2, characterized in that: The concentration of the alkaline solution is 10-20 mM.

4. The preparation method according to claim 1, characterized in that: The reaction conditions include: the reaction temperature is 140-200°C.

5. The preparation method according to claim 1, characterized in that: The reaction conditions include: the reaction time is 10 to 16 hours.

6. The preparation method according to claim 1, characterized in that: The raw material I is obtained by the following steps: mixing an iron source, an M source and water and stirring I, adding an alkali source and stirring III, to obtain the raw material I.

7. The preparation method according to claim 6, characterized in that: A surfactant is added to the mixture obtained by stirring I, and stirring II is performed.

8. The preparation method according to claim 6, characterized in that: The addition rate of the alkali source is 40 to 80 drops per minute.

9. A hydrophilic magnetic nanomaterial, characterized in that: The hydrophilic magnetic nanomaterial is prepared according to the preparation method according to any one of claims 1 to 8.

10. The hydrophilic magnetic nanomaterial according to claim 9, characterized in that: The hydrophilic magnetic nanomaterial is a magnetic nanomaterial of ferrite doped with divalent transition metal ions, and is selected from at least one of the compounds having the chemical formula shown in Formula I; M x Fe 3-x O4 formula I; The value range of x is 0.1~1.

11. The hydrophilic magnetic nanomaterial according to claim 9, characterized in that: The average particle size of the hydrophilic magnetic nanomaterial is 20-40 nm.

12. Use of at least one of the hydrophilic magnetic nanomaterials prepared by the preparation method according to any one of claims 1 to 8 or the hydrophilic magnetic nanomaterials according to any one of claims 9 to 11 in the biomedical field.

13. The use according to claim 12, characterized in that: The application is the application of the hydrophilic magnetic nanomaterial in the preparation of nuclear magnetic resonance imaging agents and / or photothermal therapy drugs.

Citation Information

Patent Citations

  • Metal doped ferrite nano material and preparation method of magnetic nano particles containing same and application thereof

    CN109626439A

  • Preparation method of iron-tungsten composite oxide nanocrystalline cluster and application thereof

    CN110507829A